Personal Well-Being among Spanish Adolescents - FERRAN CASAS (Journal of Social Research & Policy, 2012)
Although results from several samples of 12 to 16-year-old adolescents in Catalonia (region of N.E. Spain), obtained andpublished between 1999 and 2012, suggesting a constant decrease in adolescents’ subjective well-being (SWB) with age, untilnow no such data have been available for the general Spanish adolescent population. In this article we present results for arepresentative Spanish sample (N=5934), limited to students in the year of ESO (Educación Secundaria Obligatoria orCompulsory Secondary Education) (mean age = 12.09). aims of this article are twofold: (a) to validate an adaptationof the PWI for Spanish adolescents of around 12-years-old, which we will call PWI8adp; and (b) to identify variables whichshow rences in children’s subjective well-being (SWB) – using the PWI8adp as an indicator of SWB – whendichotomically comparing groups or categories of children. With this sample, among other we observe that Spanishadolescents scoring highest in subjective well-being tend to live in semi-urban environments, were born in Spain, have notrepeated a school year, live in only one family household, have two adults at home with paid employment, have parents withsecondary education or higher and have more material and cultural belongings at home compared to children with lower SWB.Furthermore, the adolescents with higher subjective well-being are those that never worry about money, think otherpeople treat them well, feel greater personal safety, feel they are listened to, report doing daily activities together with their family,do physical exercise or sport every day, have been told children have rights, have experienced fewer important recent changes intheir lives and feel their time is well organized.